Assesment of genetic variability in sugarcane (Saccharum officinarum L.) under salinity conditions - Chaudhary, Chand Pal; Singh, Sanjay; Rao, Vivekanand Pratap; Sengar, R. S. (The Indian Journal of Genetics and Plant Breeding, 2016)
An investigation was carried out to study the response of sugarcane (Saccharum officinarum L.) genotypes to morphological, physio-biochemical characters and genetic diversity at molecular level under salt stress at 8.3 dSm–1. Genotypes were grouped into three major clusters elucidating a high level of genetic diversity. Molecular analysis using SSR markers, revealed a total of 54 alleles with an average of 2.8 alleles/locus ranging from 2 to 6. Cluster I comprised 6 genotypes of which four were salt sensitive and two salts tolerant. Cluster II included two salt tolerant and one (CoS96275) salt sensitive genotype. Only one salt sensitive genotype (CoS8436) was grouped in Cluster III.The PIC value per locus ranged from 0.10 to 1.80 with an average of 0.834 for all loci. The range of enetic distance or coefficient of similarity among sugarcane genotypes were 0.25-1.00.Two genotypes (CoSe014124 and CoS767) can be used in breeding to enhance the salinity tolerance in sugarcane.